Dynamic Interaction of Train-Bridge Systems in High-Speed Railways Theory and Applications - Xia, He; Zhang, Nan; Guo, Weiwei (Advances in High-speed Rail Technology, 2018)
This book presents both the fundamental theory and numerical calculations and field experiments used in a range of practical engineering projects. It not only provides theoretical formulations and various solutions, but also offers concrete methods to extend the life of existing bridge structures and presents a guide to the rational design of new bridges, such as high-speed railway bridges and long-span bridges. Further, it offers a reference resource for solving vehicle-structure dynamic interaction problems in the research on and design of all types of highways, railways and other transport structures.